2023
DOI: 10.53378/353027
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Conceptual Understanding, Self-Efficacy and Scientific Creativity in Science Learning: A Multivariate Analysis

Albert Andry Panergayo

Abstract: This paper examined the conceptual understanding, self-efficacy, and scientific creativity of the students in Physics. The study further investigated the significant difference observed in the study variables according to sex and grade level using multivariate analysis. Using descriptive model of research design, the 125 Senior High School (SHS) students were asked to fill out the Physics Conceptual Understanding (PCU) test, Science Learning Self-Efficacy Scale (SLSE), and Scientific Creativity (SC) test. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the study of scientific creativity at the senior high school level, Panergayo (2023) revealed that Grade 12 STEM Filipino learners have average scientific creativity. This suggests that scientific creativity is fairly evident in senior high schools in the STEM field.…”
Section: Scientific Creativitymentioning
confidence: 99%
“…In the study of scientific creativity at the senior high school level, Panergayo (2023) revealed that Grade 12 STEM Filipino learners have average scientific creativity. This suggests that scientific creativity is fairly evident in senior high schools in the STEM field.…”
Section: Scientific Creativitymentioning
confidence: 99%